Passively Q-switched fibre laser utilizing erbium-doped fibre saturable absorber for operation in C-band region - Rahman, Mohd Fauzi Ab; Latiff, Anas Abdul; Rusdi, Muhammad Farid Mohd; Dimyati, Kaharudin; Harun, Sulaiman Wadi (Taylor & Francis, 2019)
In this paper, a stable and robust all-fibre passively Q-switched erbium-doped fibre laser (EDFL) emitting at 1558 nm is described. The proposed laser utilizes an 11 cm long erbium-doped fibre as saturable absorber (SA). The fibre SA features a linear optical absorption of about 13 dB in the Q-switched EDFL operating regime. By elevating the input pump power from the threshold of 60 mW to the maximum available power of 142 mW, a pulse train with a maximum repetition rate of 86 kHz, minimum pulse width of 3.39 µs, maximum average output power of 10.5 mW, maximum pulse energy of 122 nJ and maximum peak power of 36 mW are obtained. The signal to noise ratio (SNR) of the spectrum is measured to be around 70 dB. This fibre SA is simple, reliable, compact and alignment free. Thus it is suitable for making a portable pulse laser source.